2006
DOI: 10.1364/ol.31.000613
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal anisotropy of the photoinduced molecular migration in azobenzene polymer films

Abstract: The effects of tightly focused, higher-order laser beams on the photoinduced molecular migration and surface deformations in azobenzene polymer films are investigated. We demonstrate that the surface relief is principally triggered by longitudinal fields, i.e., electric fields polarized along the optical axis of the focused beam. Our findings can be explained by the translational diffusion of isomerized chromophores when the constraining effect of the polymer-air interface is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 15 publications
1
53
0
Order By: Relevance
“…This effect is believed to result from the light-induced trans – cis – trans isomerization cycles of the azo-unit, associated with random molecular reorientations, which continue until the rod-like trans -isomer becomes perpendicular to the electric field vector and thus stops absorbing light (although alternative ideas have also been put forward, see, for example, refs 3, 4). In 1995, however, another subtler phenomenon was observed in these materials56, namely a light-induced molecular displacement (or 'mass migration') occurring on the polymer-free surface and leading to the formation of stable-patterned surface reliefs78910. A fingerprint of this phenomenon is the conservation of volume: protrusions and hollows appearing on the sample surface preserve the polymer volume on the mesoscopic length scale.…”
mentioning
confidence: 99%
“…This effect is believed to result from the light-induced trans – cis – trans isomerization cycles of the azo-unit, associated with random molecular reorientations, which continue until the rod-like trans -isomer becomes perpendicular to the electric field vector and thus stops absorbing light (although alternative ideas have also been put forward, see, for example, refs 3, 4). In 1995, however, another subtler phenomenon was observed in these materials56, namely a light-induced molecular displacement (or 'mass migration') occurring on the polymer-free surface and leading to the formation of stable-patterned surface reliefs78910. A fingerprint of this phenomenon is the conservation of volume: protrusions and hollows appearing on the sample surface preserve the polymer volume on the mesoscopic length scale.…”
mentioning
confidence: 99%
“…Second, in the presence of longitudinal fields, the photomigration is much more effective along the z-component of the electric field because the photoactive material is more easily displaced towards a free interface. 31 Near planar plasmonic structures, such components are present in the near-field, even in the case of normal plane-wave excitation. 23 Moreover, it has been reported that the longitudinal component of the electric field can play a dominant role in the surface deformation although one order of magnitude weaker than that of the transverse component.…”
Section: Methodsmentioning
confidence: 99%
“…23 Moreover, it has been reported that the longitudinal component of the electric field can play a dominant role in the surface deformation although one order of magnitude weaker than that of the transverse component. 31 Next, we proceed to the photochemical imaging of the near-field generated by Au prisms with a more complex shape. In Figure 3, we consider two equilateral triangular prisms, one with rounded apices and a side length of 550 nm (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In order to properly analyze the experimental results, we have calculated the theoretical profile induced in the photosensitive film by the illumination of the structure. It was shown in previous works that the azobenzene-dye polymer is polarization sensitive 10,12 and undergoes topographic modifications proportional to the following quantity: 13…”
Section: Fabry-pérot-type Enhancement In Plasmonic Visible Nanosourcementioning
confidence: 99%